PRELIMINARY SCREENING OF ETHNOMEDICINAL PLANTS FOR ANTIFUNGAL ACTIVITY - REKHA SHARANAPPA; G.M.VIDYASAGAR (International Journal of Pharma and Bio Sciences, 2015)
Based on the ethno botanical survey, 285 solvent extracts from 57 ethno medicinal plants belonging to 55 genera and 34 families were subjected to preliminary screening for antifungal activity against Candida albicans and Fusarium udum using the agar well diffusion method at concentrations of 5 & 2.5 mg/ml. Among 57 plants, some plants extracts exhibited very effective, effective, moderate and weak activity against Candida albicans and Fusarium udum. Among the plants tested, maximum activity was observed in all the solvents extracts of Argemone mexicana, Allium sativum, Lantana camara, Tephrosia purpurea and Withania somnifera. The results of the present study indicate that the extracts of different parts of 57 ethnomedicinal plants have more potential of antifungal activity and are concentration dependent. The demonstration of a broad spectrum of these plants may help to discover new chemical classes of antibiotic substances that could serve as selective agents for infectious disease chemotherapy and control.